2015
DOI: 10.7763/ijcea.2015.v6.442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Loading, Temperature and Surface Treatment on Moisture Absorption of CFB Fly Ash Reinforced Thermoset Composite

Abstract: Abstract-Coal combustion is widely used in the Philippines and is a major contributor to power generation due to its low cost; however, it produces wastes such as emissions and fly ash (FA). Traditional fuel combustion uses pulverized coal (PC) boilers while modern technology involves the use of circulated fluidized bed (CFB) boilers which produce less emissions and are more efficient. However, the fly ash produced from CFB combustion has limited application to the construction industry as opposed to PC FA whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…27 It has been observed that moisture absorption increases with rise in temperature. 28 An eco-friendly polymer-based composite was synthesized and their properties before and after immersion in different chemical solvents were investigated. 29 The bamboo fibre/NCC­modified UP composites were showed that with adding 5 wt.…”
Section: Introductionmentioning
confidence: 99%
“…27 It has been observed that moisture absorption increases with rise in temperature. 28 An eco-friendly polymer-based composite was synthesized and their properties before and after immersion in different chemical solvents were investigated. 29 The bamboo fibre/NCC­modified UP composites were showed that with adding 5 wt.…”
Section: Introductionmentioning
confidence: 99%
“…The humidity diffusion is influenced by different parameters like the temperature; [6,7] proved that the augmentation of the temperature induces an increase of the diffusion coefficient and the amount of absorbed humidity, as it provides more agitation to the diffusing molecules [8]. Likewise, the pressure effect in the hygrothermal behavior of a composite material is investigated: [9] demonstrated that the rise of the hydrostatic pressure accelerates the diffusion phenomena, as a result the diffusion parameters increases.…”
Section: Introductionmentioning
confidence: 99%